2014
DOI: 10.1002/2014gl061109
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electric field structures in the inner magnetosphere

Abstract: Van Allen Probes observations are presented which demonstrate the presence of nonlinear electric field structures in the inner terrestrial magnetosphere (<6 R E ). A range of structures are observed, including phase space holes and double layers. These structures are observed over several Earth radii in radial distance and over a wide range of magnetic local times. They are observed in the dusk, midnight, and dawn sectors, with the highest concentration premidnight. Some nonlinear electric field structures are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
94
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 41 publications
3
94
0
Order By: Relevance
“…Recent observations by the Van Allen Probes have demonstrated that a wide variety of electric field structures and nonlinear waves regularly occur in the terrestrial inner magnetosphere. Such structures and waves include electron double layers [ Mozer et al , ], nonlinear whistler mode waves [ Mozer et al , ], kinetic‐scale field line resonances [ Chaston et al , ], electron phase space holes [ Malaspina et al , ], relativistic electron double layers [ Malaspina et al , ], and strong double layers [ Malaspina et al , ]. These structures and waves are readily identified in high‐cadence burst waveform data [ Mozer et al , ] or in spectral data as broadband wave power [ Malaspina et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations by the Van Allen Probes have demonstrated that a wide variety of electric field structures and nonlinear waves regularly occur in the terrestrial inner magnetosphere. Such structures and waves include electron double layers [ Mozer et al , ], nonlinear whistler mode waves [ Mozer et al , ], kinetic‐scale field line resonances [ Chaston et al , ], electron phase space holes [ Malaspina et al , ], relativistic electron double layers [ Malaspina et al , ], and strong double layers [ Malaspina et al , ]. These structures and waves are readily identified in high‐cadence burst waveform data [ Mozer et al , ] or in spectral data as broadband wave power [ Malaspina et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results from the Van Allen Probes mission showed that the occurrence of energetic ion injections inside geosynchronous orbit can be very frequent throughout the main phase of a geomagnetic storm and indicated that the contribution of such injections to the pressure buildup could be substantial [ Gkioulidou et al , ; Yu et al , ]. Also, various wave modes and electrostatic structures have been observed in the vicinity of injection fronts inside geosynchronous orbit [ Mozer et al , ; Chaston et al , ; Malaspina et al , ]. These waves could potentially accelerate the electron seed population up to MeV energies and contribute to the enhancement of the radiation belts [e.g., Reeves et al , ; Thorne et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, most of the studies have addressed strong or ion acoustic double layer in magnetized plasmas (see for example [3][4][5][6][7] while the mechanism of weak two dimensional double layer formation is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%